1998
DOI: 10.1001/archpsyc.55.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Physiology of Children and Adolescents With Anxiety Disorders

Abstract: These findings on the association between ventilatory physiology and anxiety disorders in children and adolescents are consistent with results from studies of adults with panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 50 publications
7
50
1
Order By: Relevance
“…Neurobiological studies of pediatric anxiety have been limited to OCD, with the exception of recent work by Pine and colleagues examining ventilatory physiology in children and adolescents with anxiety disorders. Anxious children and adolescents had higher respiratory rates and minute ventilation on CO 2 challenge and more variable breathing patterns than healthy controls; similar results have been found in studies of adult panic disorder [Pine et al, 1998b].…”
Section: Biologicalsupporting
confidence: 82%
“…Neurobiological studies of pediatric anxiety have been limited to OCD, with the exception of recent work by Pine and colleagues examining ventilatory physiology in children and adolescents with anxiety disorders. Anxious children and adolescents had higher respiratory rates and minute ventilation on CO 2 challenge and more variable breathing patterns than healthy controls; similar results have been found in studies of adult panic disorder [Pine et al, 1998b].…”
Section: Biologicalsupporting
confidence: 82%
“…Moreover, these results indicate that ovarian hormones do not necessarily protect against the effects of early life stress on respiratory control development. In light of the present data, we propose that, with such enhancement of the CO 2 chemoreflex, NMS rats may be more susceptible to develop respiratory disorders associated with neural control dysfunction such as respiratory instability during sleep or panic attacks (10,13,19,28,32). Should data support this hypothesis, NMS may be a valuable model to understand these pathologies.…”
Section: Nms and Sex-specific Plasticity Of The Hypercapnic Ventilatomentioning
confidence: 57%
“…Two studies in more than 100 children and adolescents demonstrated such perturbations in separation anxiety disorder but not social anxiety disorder. [127][128][129][130] Moreover, a series of epidemiological studies also link the diagnosis of separation anxiety disorder to various conditions, such as asthma, that produce respiratory perturbations. [131][132][133][134] Although findings in this area probably appear stronger than for either family-based or longitudinal studies, even here, support for grouping the two entities is only moderate.…”
Section: Developmental Expressions Of Pd Diathesismentioning
confidence: 99%